2019
DOI: 10.1016/j.virusres.2019.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Drug repurposing for new, efficient, broad spectrum antivirals

Abstract: Emerging viruses are a major threat to human health. Recent outbreaks have emphasized the urgent need for new antiviral treatments. For several pathogenic viruses, considerable efforts have focused on vaccine development. However, during epidemics infected individuals need to be treated urgently. High-throughput screening of clinically tested compounds provides a rapid means to identify undiscovered, antiviral functions for wellcharacterized therapeutics. Repurposed drugs can bypass part of the early cost and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 174 publications
0
68
0
Order By: Relevance
“…A combination of live cell imaging and CLEM unveiled that nascent reovirus replication organelles, known as viral inclusions (VI) are made of aggregates of tubules and vesicles originated by remodeling of the peripheral endoplasmic reticulum and that two reovirus non-structural proteins, σNS and μNS, are responsible for ER remodeling (Tenorio et al, 2018). Besides, CLEM has great potential for evaluating compounds to treat viral infections (Berger et al, 2014;García-Serradilla et al, 2019;Lowen et al, 2018;Martínez et al, 2014). For those interested in performing CLEM of virus-infected cells, detailed, step-by-step CLEM workflows describing sample preparation, imaging and correlation, have been published recently (Hellstr€ om et al, 2015;Santarella-Mellwig et al, 2018).…”
Section: Correlative Light and Electron Microscopymentioning
confidence: 99%
“…A combination of live cell imaging and CLEM unveiled that nascent reovirus replication organelles, known as viral inclusions (VI) are made of aggregates of tubules and vesicles originated by remodeling of the peripheral endoplasmic reticulum and that two reovirus non-structural proteins, σNS and μNS, are responsible for ER remodeling (Tenorio et al, 2018). Besides, CLEM has great potential for evaluating compounds to treat viral infections (Berger et al, 2014;García-Serradilla et al, 2019;Lowen et al, 2018;Martínez et al, 2014). For those interested in performing CLEM of virus-infected cells, detailed, step-by-step CLEM workflows describing sample preparation, imaging and correlation, have been published recently (Hellstr€ om et al, 2015;Santarella-Mellwig et al, 2018).…”
Section: Correlative Light and Electron Microscopymentioning
confidence: 99%
“…Therefore, pharmacologic approaches for targeting key pathogenic mechanisms, such as signaling pathways, constitute a promising tactic during outbreaks of emerging pathogens. A cost-effective drug repurposing has been previously used to combat intracellular pathogens as an urgent alternative during rapidly and deadly infectious diseases: in fact, repurposed medicines may help to reduce the investments in the earlier phases of drug development, with an immediate use in the specific setting of unmet need ( García-Serradilla et al 2019 ; Mercorelli et al 2018 ). For instance, an accumulated experience on repurposed therapeutics during previous outbreaks caused by Ebola virus, dengue virus, severe acute respiratory syndrome coronavirus (SARS-CoV), Zika virus, and Middle Eastern respiratory syndrome coronavirus (MERS-CoV) has led to the establishment of a rationale for synergistic drug combinations ( Branche et al 2018 ; Bai and Hsu, 2019 ; Cheng et al 2016 ; Xu et al 2016 ; Dyall et al 2017 ).…”
Section: Drug Repurposing As a Substitute Solution For Emerging Viralmentioning
confidence: 99%
“…The rationale for using kinase inhibitors in COVID-19 is principally based on their ability to inhibit host intracellular-viral events particularly during trafficking induced during the viral life cycle ( Pu et al 2018 ). Viruses commonly use a number of host kinases during their invasion and thus, they are considered as potential targets for kinase inhibitors repurposing as broad-spectrum antivirals ( Shor and Einav, 2018 ; García-Serradilla et al 2019 ). Several previous reports demonstrated potent antiviral properties for kinase inhibitors in various virus-induced diseases, including SARS-CoV infections (Dyallet al 2014; Badia et al 2016 ; Clark et al 2016 ; Kindrachuk et al 2015 ; Neveu et al 2012 ; Neveu et al 2015 ; Bekerman et al 2017 ).…”
Section: Potential Anticancer Drugs For Covid-19mentioning
confidence: 99%
“…Investigation into approved drugs for new therapeutic indications, which is also known as drug repurposing, has been proved to be a practical strategy in the situation of an outbreak such as COVID-19 [3][4]. Danoprevir is a potent hepatitis C virus (HCV) protease inhibitor with an IC 50 of 0.29 nM against HCV protease [5] and was approved and marketed in 2018 in China as an oral direct-acting antiviral agent to treat hepatitis C. The results of a phase 3 clinical trial with 140 patients showed that the triple regimen of ritonavir-boosted danoprevir plus pegylated-interferon a-2a and ribavirin produced a sustained virologic response (SVR12) rate of 97.1% after 12-week treatment in non-cirrhotic hepatitis C virus (HCV) genotype 1-infected Chinese patients [6].…”
Section: Introductionmentioning
confidence: 99%